An Overview of the HomePlug AV2 Technology - Larry Yonge; Jose Abad; Kaywan Afkhamie; Lorenzo Guerrieri; Srinivas Katar; Hidayat Lioe; Pascal Pagani; Raffaele Riva; Daniel M. Schneider; Andreas Schwager (Journal of Electrical and Computer Engineering)
HomePlug AV2 is the solution identified by the HomePlug Alliance to achieve the improved data rate performance required by the new generation of multimedia applications without the need to install extra wires. Developed by industry-leading participants in the HomePlug AV Technical Working Group, the HomePlug AV2 technology provides Gigabit-class connection speeds over the existing AC wires within home. It is designed to meet the market demands for the full set of future in-home networking connectivity. Moreover, HomePlug AV2 guarantees backward interoperability with other HomePlug systems. In this paper, the HomePlug AV2 system architecture is introduced and the technical details of the key features at both the PHY and MAC layers are described. The HomePlug AV2 performance is assessed, through simulations reproducing real home scenarios.